Saffron (Crocus sativus L.): as an antidepressant - Siddiqui, Mohammad Jamshed Ahmad; Saleh, Mohammed S M; Basharuddin, Siti Nur Balqis; Zamri, Siti Hajar; Mohd Najib, Mohd Hamizan; Che Ibrahim, Muhammad Zakirin; Mohd Noor, Nur Ain; Mazha, Hanin Nadiah; Mohd Hassan, Norazian; Khatib, Alfi (Wolters Kluwer - Medknow, 2018)
Saffron, Crocus sativus (Iridaceae), is a perennial herb, which earned its popularity as both medicine and spice. It is an inhabitant of different mountainous regions of Asia Minor to Greece, Western Asia, Egypt, and India. The benefits of saffron as an antidepressant are well-documented. Almost 150 volatile and nonvolatile compounds are obtained from the chemical analysis of this plant. Fewer than 50 constituents elucidated and identified so far showed phytochemical characteristics. The major bioactive compounds identified are safranal, crocin, and picrocrocin, which are responsible for its aroma as well as its bitter taste. This review is an attempt to encompass the methods of analysis and pharmacodynamic and pharmacokinetic properties of saffron followed by its efficacious and safe potential.